Defense against Cache-Based Side Channel Attacks for secure cloud computing - Chouhan, M. (Asian Research Publishing Network, 2016)
Cloud computing is a combination of various established technologies like virtualization, dynamic elasticity, broad band Internet, etc. to provide configurable computer resources as a service to the users. Resources are shared among many distrusting clients by abstracting the underlying infrastructure using virtualization. While cloud computing has many practical benefits, resource sharing in cloud computing raises a threat of Cache-Based Side Channel Attack (CSCA). In this paper a solution is proposed to detect and prevent guest Virtual Machines (VM) from CSCA. Cache miss patterns were analyzed in this solution to detect side channel attack. Notification channel between client and cloud service provider (CSP) is introduced to notify CSP about the consent of client for running the prevention mechanism. Cache decay mechanism with random decay interval is used as a prevention mechanism in the proposed solution. The performance of the proposed solution is compared with previous solutions and the result indicates that this solution posses least performance overhead with a constant detection rate and compatible with existing cloud computing model. Â© 2006-2016 Asian Research Publishing Network (ARPN).